Strategy Of Management Forest Industry Collaboration Between Segati Village Community With Pt. Rapp Sub-District Langgam District Pelalawan Province Riau - Masitah '; Defri Yoza; M. Mardhiansya ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Development of Industrial timber plantation (HTI) which give effect to the social, economic and environmental. The positive impacts are characterized by employment and the negative impact that is characterized by social conflict firms with community. One of to overcome this is to create a synergistic collaboration between company and community. This study aims to determine the forms of cooperation that occurred between the villagers of Segati with the company management and HTI management collaboration strategy to align the company with the community. Data is collected in this study conducted by direct interview to the respondents that referred to in the questionnaires. Data were analyzed using percentage analysis and SWOT analysis later described. The results showed that co-operation is done in the conservation area management and community empowerment. Collaboration have been done less than the maximum due to low participation and communication community are very less. Strategy that can be done is to involve local community in all activities of the collaboration is not against a particular group. Keywords: Strategy, collaboration, HTI, SWOT.